Penerapan Pembelajaran Kooperatif Tipe Jigsaw untuk Meningkatkan Kemampuan Sosial dan Akademik Siswa MI Islamiyah Banat - Afida, Febrian Nafisa Nurul (Madrasah Ibtidaiyah Education Journal, 2024)
Education plays a crucial role in shaping students' character and abilities, both academically and socially. In the era of globalization, social skills such as collaboration and communication have become very important. Cooperative learning, especially the Jigsaw model, is proposed as an effective method to achieve this goal. In Jigsaw learning, students are divided into small groups, where each member is responsible for studying and teaching certain parts of the material to their friends. This research uses a Classroom Action Research (PTK) approach to evaluate the implementation of the Jigsaw model at Madrasah Ibtidaiyah (MI) Islamiyah Banat, with a focus on improving students' social and academic abilities. The results show that the Jigsaw model improves students' communication, collaboration, and empathy skills, as well as increasing motivation and academic achievement. Although there are challenges in implementation, the teacher's role as a facilitator is very important to ensure that all students are actively involved. It is hoped that this research can provide recommendations for the development of better learning methods in elementary schools, creating a generation that is intelligent and has noble character.